Acupotomy therapy for cervical vertigo: A protocol for a systematic review and meta-analysis - Xie, Rongfang (Medicine (Baltimore), 2020)
BACKGROUND: Acupotomy has been widely used to relieve cervical vertigo (CV). However, the efficacy of acupotomy for CV is uncertain. The purpose of this study is to evaluate the efficacy and safety of the acupotomy for CV. METHODS: The following electronic databases will be searched to identify relevant randomized controlled trials (RCTs) for inclusion in the review from inception to April 2020: PubMed, the Cochrane Library, Embase, the China National Knowledge Infrastructure, Wanfang Database, Chinese Science and Technology Periodical Database, and Chinese Biomedical Literature Database. Two researchers will independently select studies, collect data, and assess the methodology quality by the Cochrane risk of bias tool. Meta-analysis will be completed by RevMan V.5.3 software. RESULTS: This systematic review will provide an assessment of the current state of acupotomy for CV, aiming to assess the efficacy and safety of acupotomy for Patients with CV. CONCLUSION: This systematic review will provide a credible Evidence-based for the clinical treatment of CV with acupotomy. PROSPERO registration number: CRD42019134712.